2020
DOI: 10.1016/j.devcel.2020.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis-Independent Glucose Metabolism Distinguishes TE from ICM Fate during Mammalian Embryogenesis

Abstract: Highlights d TE formation in mouse embryos is controlled by glucose metabolism activating CDX2 d Glycolysis is dispensable, and glucose is not required for amino acid or lipid synthesis d Nucleotides synthesized from glucose, along with S1P, activate mTOR and TFAP2C d Glucose metabolism by the HBP controls YAP1, which, together with TFAP2C, activates CDX2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 95 publications
(99 reference statements)
2
108
0
Order By: Relevance
“…The only previous attempt to elevate O-GlcNAcylation in pre-implantation embryos used the alternative OGA inhibitor PUGNAc [ 26 ], which is known to exhibit off-target effects [ 47 ]. In common with our study, Pantaleon et al also used immunostaining with RL2 anti-O-GlcNAcylated protein antibody and showed nuclear and nuclear membrane localisation, as did more recent studies [ 27 , 28 , 29 ]. These localisations likely reflect a concentration of O-GlcNAcylated proteins in nuclear pore complexes [ 48 ], which play important roles in early embryogenesis [ 27 , 28 ], and among DNA-associated proteins such as transcription complexes and histones [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The only previous attempt to elevate O-GlcNAcylation in pre-implantation embryos used the alternative OGA inhibitor PUGNAc [ 26 ], which is known to exhibit off-target effects [ 47 ]. In common with our study, Pantaleon et al also used immunostaining with RL2 anti-O-GlcNAcylated protein antibody and showed nuclear and nuclear membrane localisation, as did more recent studies [ 27 , 28 , 29 ]. These localisations likely reflect a concentration of O-GlcNAcylated proteins in nuclear pore complexes [ 48 ], which play important roles in early embryogenesis [ 27 , 28 ], and among DNA-associated proteins such as transcription complexes and histones [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…These data could reflect O-GlcNAcylation of the cAMP-responsive protein kinase A (PKA), which has been identified to increase PKA activity and enhance the downstream signalling that promotes STB differentiation [ 60 ]. Alternatively, O-GlcNAcylation could regulate nuclear localisation of differentiation determinants in mouse and human trophoblast, as was seen for YAP1 in the mouse early TE [ 27 ], or chromatin accessibility through histone modification as observed during mouse trophoblast stem cell differentiation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, we have shown that metabolism impacts several signaling processes that control preimplantation development (Chi et al, 2020;Nagaraj et al, 2017). For example, at the 2-cell stage, ZGA requires a novel pyruvate-mediated translocation of mitochondrial TCA cycle enzymes to the nucleus (Nagaraj et al, 2017), where these enzymes generate metabolites essential for the epigenetic changes and required for genome-level reprogramming of transcription.…”
Section: Introductionmentioning
confidence: 99%
“…For example, at the 2-cell stage, ZGA requires a novel pyruvate-mediated translocation of mitochondrial TCA cycle enzymes to the nucleus (Nagaraj et al, 2017), where these enzymes generate metabolites essential for the epigenetic changes and required for genome-level reprogramming of transcription. Later, at the morula stage, a glucose-mediated signaling process is critical for the control of expression of transcription factors necessary for TE, but not ICM, cell differentiation, and this distinction facilitates the first cell fate-choice of the embryo (Chi et al, 2020). In this manuscript, we present the first comprehensive stable isotope-resolved metabolomic analysis across all stages of preimplantation development and correlate these results with transcriptomic analysis to characterize the capacity of the embryo to reprogram its metabolism during normal development and in response to changes in the environment.…”
Section: Introductionmentioning
confidence: 99%